An Analysis Types of Onomatopoeia Words in Batman & Spiderman Comic - Komang Puspayoga; Ni Wayan Suastini (ELITE Association Indonesia, 2023)
Language is the most important thing used daily by humans to communicate directly or indirectly. Quite a lot of research that discusses language and one of them is onomatopoeia. Onomatopoeia is an object or action based on sound imitation associated with the object or action. It can be divided into four types; Mechanical Onomatopoeia, Fast Motion Onomatopoeia, Musical Onomatopoeia, and Fighting Onomatopoeia. The article entitled “An Analysis Types Onomatopoeia Word in Batman & Spiderman Comic”, aims to identify the types of onomatopoeia words found in Batman & Spiderman Comic. To analyze the data, the main theory used in this article is the onomatopoeia theory proposed by Elizabeth (2013). This study uses a Descriptive qualitative method to present descriptive and qualitative data to support the data contained in Batman & Spiderman. The results of this study indicate the types of onomatopoeia which include Mechanical, Fast Motion, Musical, and Fighting Onomatopoeia. Of the 29 data found in Batman & Spiderman Comic, the onomatopoeia type of Fighting mostly occurred with 18 data, followed by mechanical onomatopoeia with 3 data, musical with 6 data, and fast motion with 2 data. Keywords: language, onomatopoeia, type of onomatopoeia